PARTICLE IDENTIFICATION AND SCATTERING ANGLE DETERMINATION IN CHARGE-EXCHANGE (³He, t) REACTION - NGUYEN , TUAN KHAI; BUI , DUY LINH; DO , CONG CUONG; LE , XUAN CHUNG (Nuclear Science and Technology, 2013)
Charge-exchange (3He, t) reaction experiment at 0 deg. and incident energy > 100 MeV/nucleon is shown as a good probe for the GT transitions with no limitation on energy value Q. The research is based on assuming on isospin symmetry in the isobaric nuclei. The paper shows two important analysis in the (3He, t) reaction experiment. Particle identification based on energy loss and time of flight measurements. Determination of scatterred particles at very small angles, approximately 0 deg.